Evaluation of muscle thickness of the vastus lateralis by ultrasound imaging following blood flow restricted resistance exercise. (21st May 2021) - Young, Teigue R.; Duncan, Brittany T.; Cook, Summer B.
Abstract: Background: Blood flow restricted (BFR) exercise results in transient muscle growth that may be due to metabolite accumulation, hyperaemia and muscle damage, possibly serving as a stimulus for hypertrophy. Understanding the duration of this growth is important for exercise recovery and measurement of hypertrophy. Purpose: To measure changes in muscle size via ultrasound throughout a 48‐h period after a session of BFR knee extension (KE) exercise. Methods: Muscle thickness of the vastus lateralis (VL) was measured via ultrasound in 12 participants (six males and six females, age: 20.3 ± 1.1 years) before and immediately, 10 min, 30 min, 1, 3, 8, 24, and 48 h after unilateral exercise. One leg served as a non‐exercise control while the other leg performed four sets of unilateral BFR KE at 30% of one‐repetition maximum with a pressurized cuff applied to the proximal thigh and inflated to 50% arterial occlusion pressure. Results: Vastus lateralis thickness was 34.9 ± 7.2% higher immediately after exercise, 28.6 ± 7.9% at 10 min, 25.2 ± 6.1% at 30 min, 14.9 ± 4.8% at 1 h and 11.8 ± 5.6% at 3 h ( p < 0.05). There were no changes compared to pre‐exercise measurements past 3 h, and the control limb did not change ( p > 0.05). The muscle thickness of the exercise leg was significantly greater than that of the control leg from immediately after exercise up to 1 h post‐exercise ( p < 0.05). Conclusion: Muscle thickness of the VL increases for 3 h post‐BFR exercise and returns to normal within 8 h. This timeframe should be considered when prescribing exercise and planning muscle hypertrophy assessments.